Comparing the innovation and export performance of Hungarian family and non-family enterprises: Experiences drawn from empirical surveys - Judit Csákné Filep; László Radácsi; Áron Szennay (Administrative Sciences, 2023)
Family enterprises are considered to be one of the oldest and still dominant forms of business organisations. However, their innovation activity is an emerging area of research, especially in the Central and Eastern European region. The aim of our study is to address this research gap by investigating, with the help of statistical tools, the relationship between the familiness of the firms, their innovation activity, and their export activity on representative samples of Hungarian SMEs in the years 2017, 2020, and 2022. Our results suggest that the innovation activity of exporting Hungarian SMEs is more significant than that of non-exporting SMEs. However, the relationship between familiness and innovation activity is not uniform in the three analyzed years, and the relationship between familiness and export activity is not significant. The findings of this study, that firms' innovation and exporting activities can be mutually reinforcing, can be used by policymakers, curriculum developers in business education, and entrepreneurs. One of the main limitations of our research is that the 2020 and 2022 surveys were conducted after the first wave of the COVID-19 pandemic and the shock of the Russian-Ukrainian war, respectively; thus, the decisions of the firms could have been influenced by the unpredictability of the external environment.
Keywords: 350; export activity; family business; innovation